2017
DOI: 10.5223/pghn.2017.20.3.204
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Colonoscopic Retrieval of a Foreign Body in Children: A Button Battery and an Open Safety Pin

Abstract: Ingestion of foreign body in children is a relatively common problem among paediatric population. The foreign bodies mostly pass spontaneously through the gastrointestinal tract. However, complications can occur according to its anatomical location, the characteristics of the foreign body, and delays in management. Although the cases of ingested button batteries or sharp objects impacted at the gastrointestinal tract can be very serious, there have been very only a few cases have reported colonoscopic removal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 18 publications
(20 reference statements)
0
17
0
Order By: Relevance
“…Two cases were described by Lee et al . [ 6 ] and the others registered in the Navia-López et al . study [ 7 ].…”
Section: Discussionmentioning
confidence: 93%
“…Two cases were described by Lee et al . [ 6 ] and the others registered in the Navia-López et al . study [ 7 ].…”
Section: Discussionmentioning
confidence: 93%
“…The transit through the gastrointestinal tract is completed spontaneously in an average of 3.6 days [ 4 ]. Nevertheless, FB can impact at some point, causing dangerous consequences: about 20% of cases impact within the oesophagus where the FB can cause the formation of bronchoesophageal fistula, aortoesophageal fistula, oesophageal perforation with subsequent mediastinitis or abscess, complete oesophageal stricture or oesophageal obstruction, pulmonary oedema, oesophageal diverticulum [ 10 , 11 ]. The probability of impaction depends on the quality, shape, size of the foreign body, and the child's medical status.…”
Section: Discussionmentioning
confidence: 99%
“…The multiple possibilities occurring in the management of a child, who had ingested a foreign body, require complex skills for the paediatric surgeon, including the decision between intervention or not, experience in endoscopic retrieval, and in dealing with potentially life-threatening complications. The requirement of surgery or endoscopy, due to impaction, has not been quantified so far but it is estimated that about 20% of ingested foreign bodies may require endoscopic retrieval and in 1% of cases even surgical intervention [ 11 ]. Considering safety pins, it has been reported that 41% of safety pins transit spontaneously, 28.5% need an endoscopy, and 30.5% require surgical intervention [ 13 ], with the latter being more frequent in the case of open pins.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most endoscopic literature involving ingested inedible foreign objects relate to upper gastroscopy for removal of large, sharp or ulcerating objects that are pre-pyloric [ 7 , 8 ]. One report describes colonoscopy in children for a button cell and safety pin removal from the terminal ileum [ 9 ]. Objects >2–2.5 cm in diameter tend not to pass through the pylorus or ileocecal valve, and objects longer than 5–6 cm are restricted by the duodenal sweep [ 5 ].…”
Section: Discussionmentioning
confidence: 99%